Dynamic variation of nutrient absorption, metabolomic and transcriptomic indexes of soybean (Glycine max) seedlings under phosphorus deficiency. Issue 2 (10th April 2023) - Li, Mingxia; Zhou, Ji; Liu, Qi; Mao, Lili; Li, Haoru; Li, Shuying; Guo, Rui
Abstract: The dynamic trajectory of metabolites and gene expression related to phosphorus absorption and utilization in soybean seedling roots were determined under short- and long-term phosphorus deficiency stress. The metabolome results showed that TCA and GS/GOGAT cycles were enhanced after 2 days of phosphorus deficiency stress; however, they were inhibited after 15 days. GC-TOF-MS showed that phosphorus deficiency increased the accumulation of amino acids significantly after 2 days, whereas organic acids and lipid substances increased significantly after 15 days. Quantitative reverse transcription-polymerase chain reaction (RT-PCR) showed that transcriptional levels of five key genes related to phosphorus activation and phosphorus starvation signal transduction increased continuously with phosphorus deficiency. The expression of GmPHT1 and GmSPX triggered the phosphorus starvation signal pathway and induced the expression of the GmPS and GmPAP genes to enhance the synthesis and secretion of organophosphorus hydrolase and organic acid in soybean roots under phosphorus deficiency. The phospholipid metabolism was enhanced significantly after 15 days of stress and when GmSQD, a crucial enzyme in lipid biosynthesis, was up-regulated. Thus, we propose that future investigations on stress caused by phosphorus deficiency should include more organs obtained at different developmental stages. Abstract : In our study, the dynamic trajectories of metabolites and gene expression related to phosphorus uptake and utilization in soybean seedling roots under phosphorus deficiency were determined by comparing growth parameters, mineral nutrient contents, metabolism and transcription levels at different growth and development stages. The study identified metabolites, metabolic pathways and genes that play a key role in short- and long-term phosphorus deficiency stress in soybean. This study can provide important reference values for improving soybean stress resistance.